Ralph Thomlinson. Urban structure : the social and spatial character of cities. Nueva York : Random House, 1969. 335 p. - Unikel Spector, Luis (Estudios Demográficos y Urbanos, 1970)
RALPH THOMLINSON, Urban Structure. The Social and Spatial Character of Cities, Nueva York, Random House, 1969.